Content Alert System Using Short Message Service (SMS): A Testimony of two Collaborative Projects in Africa and Asia - Anbu, John Paul; Jetty, Sridevi (My University, 2013)
This paper is a case study of a semi-automated Content Alert System implemented at two university libraries; The university of Swaziland, Swaziland, Southern Africa and Bundelkhand University Library at Jhansi in India. Among the various mobile services, Short Message Service (SMS) is one of the most popular services widely used all over the world. The projects initiated at these libraries were intended to use the SMS service to provide an effective content alert system with very little cost impact on the libraries and at the same time aimed to increase the usage of library resources among the library patrons. The project ran in two phases. In the first phase a successful content alert system was tried and tested at the University of Swaziland with the help of Emerald Publishers. On successful completion of the project a prototype was developed. Using the prototype the second phase of the project was designed. In the second phase a similar content alert service was established with a larger user group and the alerts were generated from a number of publishers and SMSs were sent to the patrons. This paper describes in detail the background, the rationale, details of the project, the methods used and the findings of the projects.
Keywords: Short Message Service; SMS; Mobile Computing; Mobile library applications